COUGH IN CHILDREN: DIAGNOSTICS AND MANAGEMENT - K. S. Volkov; L. L. Nisevich; L. S. Namazova-Baranova; E. G. Filyanskaya; A. A. Alekseeva; V. A. Barannik (Вопросы современной педиатрии)
Despite the constant interest of the specialists to the problem of cough, it is still very topical, as the causes of cough are continued to study, the diagnostics algorithms to its detection and approaches to its treatment are defined. Different causes of cough development in children according to their age are discussed in this article, as well as the directions of the diagnostic search and approaches to the therapy of coughing syndrome in children are explained. A special emphasis is put on symptomatic drugs. The choice of drug depends on the type of cough, of its intensity and other characteristics.